Hydrophilic interaction liquid chromatography coupled with tandem mass spectrometry method for the simultaneous determination of l‐valine, l‐leucine, l‐isoleucine, l‐phenylalanine, and l‐tyrosine in human serum. Issue 22 (16th October 2015) - Sun, Luning; Jiao, Huiwen; Gao, Beibei; Yuanzi, Qingyun; Zhang, Hongwen; Wang, Yongqing; Ou, Ning; Yan, Zhengyu; Zhou, Hongwen
Abstract : l ‐Valine, l ‐leucine, l ‐isoleucine, l ‐phenylalanine, andl ‐tyrosine are important proposed biomarkers for the early detection and diagnosis of type 2 diabetes. A simple and selective hydrophilic interaction chromatography with tandem mass spectrometry method was developed for the simultaneous determination of these amino acids in human serum, using stable isotope‐labeled amino acids as internal standards. Chromatographic separation was carried out on a Syncronis HILIC column (150 mm × 2.1 mm, 5 μm) with the column temperature of 35°C and a mobile phase consisted of acetonitrile/120 mM ammonium acetate (89:11, v/v), and the run time was 11.0 min. The mass spectrometric analysis was performed using a QTRAP 5500 mass spectrometer coupled with an electrospray ionization source in positive ion mode. As these five amino acids are endogenous compounds in serum, we used the corresponding stable isotope‐labeled amino acids to evaluate the matrix effect and recovery in serum. The matrix effect was 98.7–107.3%, and the recovery was 92.7–102.3%. Calibration curves spiked unlabeled amino acids in water were linear over the range of 0.200–100 μg/mL. The accuracy, inter‐, and intraday precision were below 10.2%. Analytes were stable during the study. This assay method has been validated and applied to the early diagnosis research of type 2 diabetes.